Assessment of changes in the characteristics of the ice regime of the Lower Yenisei in contemporary climatic conditions - Vladimir V. Zuev; Valeria А. Uymanova; Dmitriy A. Vershinin; Аleksey V. Pavlinsky (Водное хозяйство России: проблемы, технологии, управление)
The area of Lower Yenisei is a part of the Russian Arctic territory, which is sensitive to modern changes of climatic conditions. Many types of economic activities are associated with the timing and duration of ice phenomena on the rivers of the Arctic zone.